(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:The use of ultrasound (US) in the assessment of thyroid disease has greatly increased the detection of small thyroid nodules unrecognized at clinical examination. Objective:To determine the accuracy of the diagnosis of the nature of solitary thyroid nodule by ultrasound in comparison with histopathological findings and to correlate the different sonographic and color-Doppler (CFD) findings with the results of histopathology of resected nodules. Methods:The nodule size, echogenicity, presence/absence of calcification, lesion margins and vascular pattern of 63 patients with solitary thyroid nodule referred for US assessment). Results:Twenty four patients (38.1%) had malignant thyroid nodules and 39 patients (61.9%) had benign nodules as confirmed by histopathology. The large nodules show benign histopathological finding more than the small nodules (no significant difference; 56.5% vs. 25.4%, respectively). Histologically-confirmed malignant lesions show hypoechoic appearance and calcification more than benign nodules. The Malignant lesions presented more frequently than did benign nodules as solid hypoechoic appearance and irregular or blurred margins (52.2% vs. 47.8%;), and intranodular vascular pattern with calcification (63.3% vs. 36.4%) and the sensitivity and specificity by ultrasound in the evaluation of these nodules will be more and have highly diagnostic accuracy (58.3%, 79.49%, 71.5% respectively) in comparison to the former feature (50%, 71.79%, 63.5% respectively). Conclusion:We conclude that the typical appearance of nodules in thyroid carcinoma is irregular hypoechoic mass with internal vascularity and calcifications. Uncommon appearances of carcinoma include hyperechoic texture, intrinsic hypovascularity, and sharp regular contours. Uncommon sonographic features were found to occur more often than expected. Keywords:Thyroid nodule, ultrasound, color Doppler